2020
DOI: 10.1186/s13148-020-00933-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial D-loop methylation levels in sporadic amyotrophic lateral sclerosis

Abstract: Background Mitochondrial dysregulation and aberrant epigenetic mechanisms have been frequently reported in neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), and several researchers suggested that epigenetic dysregulation in mitochondrial DNA (mtDNA) could contribute to the neurodegenerative process. We recently screened families with mutations in the major ALS causative genes, namely C9orf72, SOD1, FUS, and TARDBP, observing reduced methylation levels of the mtDNA regulatory region (D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 70 publications
4
35
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood collected in EDTA tubes from each subject using the QIAmp DNA blood Mini Kit (Qiagen, Milan, Italy, Catalog N° 51106) following the manufacturer’s instructions, and quantified using a Nano Drop ND 2000c spectrophotometer (NanoDrop Thermo scientific, Wilmington, DE, USA). Methylation of the D-loop region was assessed by means of methylation sensitive-high resolution melting (MS-HRM) and pyrosequencing techniques, as reported elsewhere [ 13 , 16 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genomic DNA was extracted from peripheral blood collected in EDTA tubes from each subject using the QIAmp DNA blood Mini Kit (Qiagen, Milan, Italy, Catalog N° 51106) following the manufacturer’s instructions, and quantified using a Nano Drop ND 2000c spectrophotometer (NanoDrop Thermo scientific, Wilmington, DE, USA). Methylation of the D-loop region was assessed by means of methylation sensitive-high resolution melting (MS-HRM) and pyrosequencing techniques, as reported elsewhere [ 13 , 16 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that also epigenetic modifications of the mitochondrial genome could contribute to neurodegeneration [ 10 ]. In this regard, dysregulation of mitochondrial DNA (mtDNA) methylation in the central nervous system and in peripheral blood samples of patients with AD, PD, and amyotrophic lateral sclerosis (ALS), as well as in transgenic mice modelling, has been reported [ 11 , 12 , 13 , 14 , 15 , 16 ]. The majority of these studies investigated the methylation levels of the mtDNA regulatory region (D-loop), which regulates mtDNA replication and transcription, revealing that D-loop methylation levels were dynamically dysregulated with disease progression in animal models of AD and were significantly different in human postmortem AD brains and in peripheral blood cells of living AD patients compared to healthy controls [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, another study from the same research group revealed that mtDNA methylation patterns and mitochondrial DNMT3A levels were abnormal in the skeletal muscles and spinal cord of pre-symptomatic ALS mice carrying mutations in the human superoxide dismutase 1 gene (SOD1), which included DNMT3A up-regulation, increased MT-RNR2 gene methylation and decreased D-loop region methylation [49]. Altered D-loop methylation levels have also been observed in the peripheral blood of sporadic and SOD1 ALS patients when compared to both ALS patients with mutations in FUS, TARDBP and C9orf72 and to control subjects who are noncarriers of ALS-linked gene mutations [96,100]. Regarding Alzheimer's disease, a non-significant increase in 5-hmC levels was observed in post-mortem mtDNA brain samples of seven late-onset AD patients with respect to five control subjects [93].…”
Section: Altered Mtdna Methylation In Neurodegenerative Diseasesmentioning
confidence: 99%